Penerapan model problem-based learning berbantuan media konkret dalam meningkatkan hasil belajar materi bangun ruang kelas II sekolah dasar - Felianti, Eunike Steni; Winanto, Adi (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
The selection of learning models and the use of appropriate learning media can affect student learning outcomes. The problem faced in class II SDK Satya Wacana is that student learning outcomes that achieve KKM are only 50%. This study aims to improve student learning outcomes in class II by implementing a problem-based learning model assisted by concrete media. The research method is Classroom Action Research. This study was conducted in 2 cycles with stages of planning, implementation, observation and reflection. The research subjects were conducted in class II with 22 students. Data collection was carried out by interviewing and observing student learning outcomes using the problem-based learning model. The results obtained: Student learning outcomes in cycle I: The percentage of student learning outcome completion is 68%. In cycle II, student learning outcomes with the problem-based learning model experienced changes and improvements by showing student learning outcomes with a percentage of completion reaching 86%. Based on the results obtained, it can be said that the problem-based learning model assisted by concrete media can improve student learning outcomes in mathematics material in class II SDK Satya Wacana Salatiga